Studi Kohort Kejadian Penyakit Demam Berdarah Dengue - Misti Rahayu, Tri Baskoro, Bambang Wahyudi (Berita Kedokteran Masyarakat (BKM), 2010)
Background: Dengue Hemorrhagic Fever (DHF) disease is caused by dengue virus transmitted through the bites of Ae.aegypti. At Surabaya Municipality DHF cases are increasing within the last five years. Risk factors for the prevalence of DHF are among others: 1) occupancy density, 2) availability of water tank, and 3) population behavior such as securing/keeping water tank closed, draining water tank once a week and burrying used items, sleeping in the morning and afternoon, leaving windows open from morning to evening.Objective: To identify association between three risk factors as mentioned above and the prevalence of DHF disease at Subdistrict of Sawahan, Surabaya Municipality.Method: The study was analytic observational with cohort design, involving as many as 1,092 samples of houses and 4,549 respondents from three councils at Subdistrict of Sawahan. To identify the prevalence of DHF disease, interview with respondents and direct examination were made within three subsequent months. To identify distribution of respondents and the prevalence of DHF disease, analysis was made descriptively. Chi square test was made to identify association between exposure and the prevalence of DHF disease and Risk Relative (RR) measurement was made to identify degree of association.Result: Occupancy density statistically had no association with the prevalence of DHF disease p=0.269 and RR=1.242). Availability of waste water sewage with high status of Maya Index Statistically had no association with the prevalence of DHF disease (p=1.000 and RR=1.028). Behavior of the population in keeping water tank closed, draining water once a week and burying used items p= 1.000 and RR=1.003; opening windows from morning to evening p=1.000 and RR=1.003; sleeping in the morning p=0.163 and RR=2.041; sleeping in the afternoon p=1.000 and RR=0.814; and opening windows p=1.000 and RR=1.042 showed no association with the prevalence of DHF disease.Conclusion: Factors of occupancy density, availability of water tank based on Maya Index (MI) and population behavior had no association with the prevalence of DHF disease at Subdistrict of Sawahan, Surabaya Municipality.Keywords: occupancy density, Maya Index, dengue hemorrhagic fever, behavior